Eudora Welty - American Writers 66 : University of Minnesota Pamphlets on American Writers - Bryant, J. A. (Joseph Allen), 1919-1999 (Book collections on Project MUSE., 1968)
Eudora Welty - American Writers 66 was first published in 1968. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.